Improved chemical water oxidation with Zn in the tetrahedral site of spinel-type ZnCo2O4 nanostructure. (March 2020) - Chakraborty, B.; Indra, A.; Menezes, P.V.; Driess, M.; Menezes, P.W.
Abstract: Spinel oxides with the composition of A II B III 2 O4 (A and B are metal ions) represent an important class of anode material for water splitting to replace the currently used noble-metal catalysts. Although spinel electrocatalysts have widely been investigated for electrochemical water oxidation, the role of octahedral and tetrahedral sites influencing catalytic performance has been a topic of discussion for a long time and still under debate. Lately, this issue has been addressed by substituting redox-inert cation to the tetrahedral sites of cobalt spinels and comparing the electrochemical activity between them. However, rapid surface structural transformation of the catalysts under operating electrochemical conditions makes it difficult to infer the exact contribution of tetrahedral and octahedral sites for water oxidation. Herein, for the first time, we utilize the oxidant-driven water oxidation approach to reveal the responsible active sites using two spinel-type nanostructures, Zn II Co2 III O4 and Co II Co2 III O4 (Co3 O4 ), synthesized by using a single-source precursor approach. Strikingly, a superior O2 production rate (0.98 mmolO2 molCo −1  s −1 ) following first-order reaction kinetics was achieved for ZnCo2 O4 in the presence of Ce IV as sacrificial electron acceptor compared to Co3 O4 spinel (0.29 mmolO2  molCo −1  s −1 ). The structural and morphological stability of the ZnCo2 O4 and Co3 O4 post water oxidation catalysis confirms that the catalytic activity is strictly controlled by the geometry and electronic structure of the active site of the spinel structure. The higher performance of ZnCo2 O4 over Co3 O4 further indicates that the presence of Co II is not essential for catalytic water oxidation. The presence of redox inert Zn II at the tetrahedral site of ZnCo2 O4 can facilitate the stabilization of a high-valent Co IV intermediate via oxidation of Co III (situated at the octahedral site), and this intermediate can be regarded as the active species for water oxidation catalyst along with structural defects caused by surface Zn leaching. Graphical abstract: Structurally identical spinel-type ZnCo 2 O 4 and Co 3 O 4 catalysts were used for driving oxidant-driven water oxidation, whereby the essential role of metal ions in the tetrahedral versus octahedral site in enhancing the catalytic activity has been uncovered. Image 1 Highlights: Isolation of spinel-type ZnCo2 O4 nanochains and Co3 O4 nanosphere. Oxidant-driven water oxidation by ZnCo2 O4 and Co3 O4 nanostructures using ceric ammonium nitrate (CAN). Superior OER activity of ZnCo2 O4 compared to Co3 O4 . Prominence of Zn II in the tetrahedral site during water oxidation catalyzed by octahedral Co III .